Analysis of Student Errors in Solving HOTS-Type Sequence and Series Problems Based on Newman Error Analysis - Risky Illaina Septia Putri; Ratri Candra Hastari (AlphaMath : Journal of Mathematics Education, 2022)
This study aims to analyze student errors in solving HOTS-type math problems using Newman's stages on sequence and series material. This research is qualitative. The subject of this research is class X DPIB 1 SMK "SORE" Tulungagung. Data collection techniques used are test questions and interviews. The data analysis technique was carried out by data reduction, data presentation, and conclusion. The results of this study showed that of the 29 students who were given the HOTS test questions, 3 students made the most mistakes based on the Newman stage. The three students who later became the research subjects made errors at each of Newman's stages, is reading errors (T1), problem comprehension errors (T2), transformation errors (T3), process skill errors (T4), and encoding errors (T5). Thus, it can be concluded that there are still many students in class X DPIB 1 SMK "SORE" Tulungagung who make mistakes in solving HOTS-type sequences and series questions. The implementations of this research may not have been carried out optimally. It is hoped will prepare everything as well as possible so that this research can run better.